PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PT ULTRAJAYA MILK INDUSTRY & TRADING COMPANY TBK PERIODE 2014-2024 - Sarah Apriliani; Dina Novita (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to examine the effect of capital structure and firm size on firm value at PT Ultra Jaya Milk Industry & Trading Company, Tbk for the period 2014–2024. This research employs a quantitative method. The population consists of the company’s financial statements and stock prices, while the sample was selected using based on the annual reports during 2014–2024. The data analysis techniques include descriptive analysis, classical assumption tests, multiple linear regression, correlation coefficient, t-test, F-test, and coefficient of determination. All statistical tests were conducted using SPSS version 25. The results show that partially, capital structure has a positive and significant effect on firm value, with a tcount of 3.983 greater than ttable 2.306 and a significance value of 0.004 < 0.05. Firm size has a negative and significant effect on firm value, with a tcount of –8.566 less than ttable 2.306 and a significance value of 0.000 < 0.05. Simultaneously, capital structure and firm size have a significant effect on firm value with an Fcount of 38.486 greater than Ftable 4.46 and a significance value of 0.000 < 0.05. The adjusted R² value is 0.906, which means that 90.6% of the variation in firm value can be explained by capital structure and firm size, while the remaining 9.4% is influenced by other variables not examined in this study.